Numerical simulation of a rectangular microstrip patch antenna for 3.35 GHz applications. (June 2020) - Hanafiah Rambe, Ali; Lutfi, Muhammad; Suherman,; Zulfin, Muhammad; Pinem, Maksum
Abstract: This paper described the design and numerical simulation of a rectangular microstrip patch antenna for applications at 3.35 GHz. The numerical simulation carried out with the aid of AWR software. The initial design was done by mathematical calculation. Then the initial design is modeled and numerically simulated to get the optimal design. Optimized parameters are length of the patch and width of the feed line. Based on the optimal results obtained a minimum return loss of -15.98 dB and bandwidth below the return loss of -10 dB is 93 MHz (3.311 - 3.404 GHz).